Survival of Rheumatic Heart Disease in Indonesian Children - Arafuri, Nadya; Murni, Indah Kartika; Julia, Madarina; Nugroho, Sasmito; Soehadi, Noormanto (Ubiquity Press, 2022)
Background: Rheumatic heart disease (RHD) remains a preventable cause of cardiovascular deaths in children in low- and middle-income countries. However, long-term outcome data of children with RHD is still lacking in Indonesia. Objective: To investigate the long-term outcomes of RHD, particularly the survival rates and the predictors. Methods: A retrospective cohort study was done in children aged less than 18 years old admitted with RHD at a tertiary hospital (Dr. Sardjito Hospital, Indonesia) from 2011–2021. Survival time was estimated from the date of first diagnosis of RHD to the survival endpoint (date of mortality or censoring). Kaplan-Meier curves, log-rank test and Cox-regression analysis were used for survival analysis and the predictors. Results: A total of 155 patients admitted with RHD during the study period. Of these, 14 (9.0) deaths were reported as RHD related mortality with the mean age ± standard deviation of 11.9 ± 2.9 years. Median follow up period was 16 months. The survival rate at 1, 4, and 8 years were 93, 86.1 and 60, respectively. Survival was lower in patients with severe valve lesions and NYHA functional class III-IV at the time of diagnosis. Multivariate Cox-regression analysis showed the significant predictors for mortality were poor adherence to penicillin and congestive heart failure, HR 12.7 (95CI 1.4–113.5) and 18.6 (95CI 1.8–185.0) respectively. Conclusion: Approximately, only six in 10 children are able to survive at eight years after diagnosis. Poor adherence to penicillin and congestive heart failure were predictors for death. This study emphasizes the needs to improve the adherence of children with RHD and early detection of subclinical carditis in children. © 2022 The Author(s).